Clozapine: why wait to start a laxative?. (November 2019) - Attard, Azizah; Iles, Andrew; Attard, Stephen; Atkinson, Nathan; Patel, Anita
SUMMARY: Clozapine, the antipsychotic of choice for treatment-resistant schizophrenia, has a number of side-effects, some of which are potentially life-threatening. Historically viewed as a relatively minor side-effect, there is increasing awareness of the potentially severe sequalae of constipation secondary to clozapine-induced gastrointestinal hypomotility (CIGH). These include ileus, intestinal obstruction, bowel ischaemia, gastrointestinal necrosis, toxic megacolon and death. CIGH is significantly more common than clozapine-induced blood dyscrasias and has a higher mortality rate. Although strict criteria must be followed to assertively monitor, detect and treat blood dyscrasias in patients taking clozapine, no such framework exists for CIGH. We recommend that prescribing guidelines, regulatory agencies and information from manufacturers should more clearly highlight the risks identified in the literature. Furthermore, we recommend that, in people taking clozapine, constipation should be prevented by prophylactic treatment with laxatives rather than treated only when clinically identified. LEARNING OBJECTIVES: After reading this article you will be able to: understand the mechanism of gastrointestinal hypomotility in those taking clozapine improve the monitoring of clozapine-induced constipation understand prophylactic laxative treatment and the use of less commonly prescribed laxatives in patients who experience clozapine-induced constipation. DECLARATION OF INTEREST: None.